2021
DOI: 10.1215/00703370-8917630
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effect of Time in Migration Measurement Using Georeferenced Digital Trace Data

Abstract: Georeferenced digital trace data offer unprecedented flexibility in migration estimation. Because of their high temporal granularity, many migration estimates can be generated from the same data set by changing the definition parameters. Yet despite the growing application of digital trace data to migration research, strategies for taking advantage of their temporal granularity remain largely underdeveloped. In this paper, we provide a general framework for converting digital trace data into estimates of migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Thus, the def ni tion of migrant is still not har mo nized world wide (Kupiszewska and Nowok 2008;Willekens 1994). Fiorio et al (2021) have high lighted the pos si bil ity of using geotagged Twitter data to inves ti gate short-term mobil ity and long-term migra tion. They suggested that draw ing on dig i tal trace data could help to refne migra tion the ory and mod el ing.…”
Section: Digital Traces and Their Limitationsmentioning
confidence: 99%
“…Thus, the def ni tion of migrant is still not har mo nized world wide (Kupiszewska and Nowok 2008;Willekens 1994). Fiorio et al (2021) have high lighted the pos si bil ity of using geotagged Twitter data to inves ti gate short-term mobil ity and long-term migra tion. They suggested that draw ing on dig i tal trace data could help to refne migra tion the ory and mod el ing.…”
Section: Digital Traces and Their Limitationsmentioning
confidence: 99%
“…More recently, social media platforms, such as Facebook and Twitter, became widely used in demographic studies. The popularity of these platforms as sources of data is largely determined by the coverage and accessibility that can be provided, as well as their potential to yield accurate measures (Zagheni, Weber, and Gummadi 2017;Fatehkia, Kashyap, and Weber 2018;Palotti et al 2020;Alexander, Polimis, and Zagheni 2020;Fiorio et al 2021).…”
Section: New Forms Of Datamentioning
confidence: 99%
“…Following a pioneering study using e-mail data and IP geolocation to estimate international migration flows (Zagheni and Weber 2012), new approaches to study migration and mobility that rely on social media data have emerged. They include the development of methods to use Twitter data to assess the relationship between short-term mobility and longterm relocations (Fiorio et al 2017(Fiorio et al , 2021, or to infer international migration (Zagheni et al 2014). Facebook data have been used to assess the impact of natural disasters on short-term mobility (Alexander, Zagheni, and Polimis 2019), and, more broadly, to quantify international mobility (Zagheni, Weber, and Gummadi 2017;Spyratos et al 2019).…”
Section: Introductionmentioning
confidence: 99%